Czynniki wpływające na sposób liczenia opłacalności inwestycji zagranicznych - Różański, Jerzy (The Factors that Have an Influence on the Way of Counting the Commercial Viable of the International Investmen, 2007)
Increasing division of character, sphere and direction international investments causes inclusions or exclusions, in these investments' commercial viable count, lot of elements, because of the count's substantial division. The different procedures of managing this count are proposed depending on the form of investment. The article presents the relation between the defined conditions of the international investment's realization and the method of counting this investment's commercial viable - the dilemmas and doubts connected with the implementation defined procedures and methods of counting commercial viable of the international investment are also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 461-468